Pemikiran dan Penentangan Rene Descartes terhadap Metafisika - Sarika Sandi; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to examine the understanding of rationalism that was initiated by Rene Descartes and the opposition to metaphysics, Rene Descartes' Rationalism is an understanding that emerged in the confines of the Christian church known as the scholastic period. The method used in this study is a qualitative descriptive method, and secondary data, the author tries to relate and present Descartes' rationalist thoughts and Descartes' metaphysical thoughts to prove that material things exist. Even God created humans to have a tendency to understand that material things exist. If the understanding that material things exist is only a complex matrix that deceives the human mind, then this means that God is an impostor, and for Descartes, an impostor is imperfection. Whereas God is a perfect being, therefore God cannot deceive, so that material objects must exist.